Pengaruh brand image, brand awareness, dan kualitas produk terhadap keputusan pembelian produk planet popcorn pada mahasiswa fakultas ekonomi universitas tarumanagara jakarta - Ekawati, Sanny; Aryadirda, Yoga (Jurnal Ekonomi, 2015)
This study was conducted to investigate the effect of brand image, brand awareness, and product quality on the consumer’s purchase decision. The population of this research were students of Tarumanagara University in Jakarta. The sampling frame was limited to those of the Economic Faculty. The non-probabilistic convenience sampling method was used in this research. The method of data collection was conducted by distributing questionnaires to 100 respondents. The technique of data analysis used was the multiple regression analysis. The findings of this research showed that purchase decision is positively and significantly affected by brand image, brand awareness, and product quality.